Using remote sensing data in the analysis of land use and surface temperature in the city of Manacapuru-AM - Ferreira Junior, Edinaldo Inocêncio; Lindoso, Eduardo Arival; Pereira, Matheus Bertulino (Technical and Scientific Journal Green Cities, 2024)
In the last decades, the climate has been the subject of studies in various regions of the world, especially urban climate. The increase in built-up areas combined with the decrease in vegetation, increasingly intense, contribute to the formation of a climate with distinct characteristics compared to rural areas. Therefore, the general objective of this study was to analyze, based on remote sensing data, the relationship between land use and land cover and its influence on surface temperature and NDVI of the city of Manacapuru, located in the metropolitan region of Manaus. The data were analyzed through geographic information systems, using the QGIS 3.16 Hannover software, land use and land cover data from the Mapbiomas collection 6 of 2020, and remote sensing images from the Landsat 8 satellite bands 10 TIRS, for surface temperature, and bands 4 and 5 OLI, for NDVI. The result was a predominance of urbanized areas, with a minimum surface temperature of 24.6°C, an average of 28.8°C, and a maximum of 33.1°C, with a range of 8.5°C. The NDVI ranged from -0.05 to 0.53, respectively indicating areas with absence, little, moderate, and dense vegetation. Finally, tree planting plays an important role in mitigating city temperatures, as it intercepts much of the radiation emitted by the sun, preventing heat from reaching the surface, providing thermal comfort, and on the other hand, the removal of vegetation and the intensification of urban areas increase the configuration of heat islands.